2009
DOI: 10.1371/journal.pone.0005528
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of Mycobacterium tuberculosis-Specific CD8 T-Cells in Patients with Active Tuberculosis and in Individuals with Latent Infection

Abstract: CD8 T-cells contribute to control of Mycobacterium tuberculosis infection, but little is known about the quality of the CD8 T-cell response in subjects with latent infection and in patients with active tuberculosis disease. CD8 T-cells recognizing epitopes from 6 different proteins of Mycobacterium tuberculosis were detected by tetramer staining. Intracellular cytokines staining for specific production of IFN-γ and IL-2 was performed, complemented by phenotyping of memory markers on antigen-specific CD8 T-cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
72
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 87 publications
(89 citation statements)
references
References 35 publications
15
72
2
Order By: Relevance
“…Primary data from seven TB patients (with PBMCs) stimulated with peptide 68 are shown in Supporting Information Figure 4. Thus, and differently from CD8 T cells recognizing M. tuberculosis peptides in the context of HLA-class Ia molecules [31,[34][35][36][37] In contrast, coculture of B cells with 9 of the 15 HLA-E-restricted CD8 T-cell lines resulted in a significant increase in the production of IgG and IgM. As a control, coculture of tonsillar B cells with sorted CD8 + T cells isolated from the PBMCs of healthy donors did not increase significantly Ab production.…”
Section: Functional Properties Of Hla-e-restricted and M Tuberculosimentioning
confidence: 90%
See 1 more Smart Citation
“…Primary data from seven TB patients (with PBMCs) stimulated with peptide 68 are shown in Supporting Information Figure 4. Thus, and differently from CD8 T cells recognizing M. tuberculosis peptides in the context of HLA-class Ia molecules [31,[34][35][36][37] In contrast, coculture of B cells with 9 of the 15 HLA-E-restricted CD8 T-cell lines resulted in a significant increase in the production of IgG and IgM. As a control, coculture of tonsillar B cells with sorted CD8 + T cells isolated from the PBMCs of healthy donors did not increase significantly Ab production.…”
Section: Functional Properties Of Hla-e-restricted and M Tuberculosimentioning
confidence: 90%
“…Tetramer staining was carried out as described in detail previously [31,37,54]. PBMCs (10 6 /mL) were incubated in U-bottom 96-well plates, washed twice in PBS containing 1% FCS (Sigma), and stained for 30 min at 4°C with PE-labeled tetramers (5 μL each) prepared as previously described [31,37,54]; they were washed and subsequently stained with FITC-labeled anti-CD8 mAb (RPA-TB, BD Biosciences) and analyzed by flow cytometry on a FACSCanto.…”
Section: Tetramer Stainingmentioning
confidence: 99%
“…+ T cells contribute to M. tuberculosis control through: 1) IFN-g and TNF-a production (9,(15)(16)(17); 2) lysis of infected host cells (16)(17)(18); and 3) direct killing of mycobacteria (19)(20)(21). One study demonstrated clonal CD4 + and CD8 + T cell expansion in granulomas from subjects with latent TB infection (22), and similar changes in the TCR repertoire were reported in peripheral blood versus pleural fluid in TB patients (23).…”
Section: Following Recognition Of Mycobacterial Ags On Infected Cellsmentioning
confidence: 87%
“…In a later study, we reported similar findings for CD8 + T cells directed against six M. tuberculosis epitopes (two of which were newly identified). In that study, it was also found that M. tuberculosis peptide-specific IL-2 + /IFN-g + CD8 + T cell responses were associated with natural protection against developing TB disease (15). In parallel studies, Kaufmann and colleagues (25) found clonal expansion of effector memory CD8 + T cells in older children with TB, with potential impact on the course and severity of disease.…”
Section: Following Recognition Of Mycobacterial Ags On Infected Cellsmentioning
confidence: 88%
“…Nonspecific background was extremely low when more than one cytokine was examined. A cutoff of 0.01% was used as described previously [48]; values below this were set to zero.…”
mentioning
confidence: 99%